Análisis del convenio de la universidad técnica de cotopaxi con el servicio de rentas internas, sobre el proyecto "el intercambio de cooperación institucional entre el S.R.I Y La U.T.C" durante el periodo comprendido entre el 1 de enero al 31 de diciembre de 2017. - Gallo Chugchilán, Wilson Rolando (2018)
For some time, the way in which organizations relate has changed, its structure, design and vision of organization is different now. Big and small companies, are looking for the best way to emerge, growing and getting place in a market. They don`t do it alone, on the other hand, they need the collaboration of other institutions for providing which are the necessities, from capital investment, cost reduction, process experience, social recognition, brand positioning, the use of infrastructure, machinery and equipment, and another reasons. Collaborative alliances play a very important role in achieving to the objectives of a company, and more when they are in a beginning stage, consolidating cooperative relationships through the different association figures allows companies to develop and grow; this research sought to explore the degree of compliance with the agreement signed between Cotopaxi Technical University and Servicios de Renta Interna. To develop this work, was applied focused on observable aspects. The inductive method was applied to obtain general conclusions on general aspects, it was used several information gathering techniques such as: observation, interviews, surveys; the same ones that were applied to the people related to the object of study, in this way an in-depth analysis of the agreement was made, involving the researcher and the related parties in this alliance. This work gave as a result that the conditions fulfilled and it was determined that there is satisfaction of the taxpayers who sought guidance and advice in the NAF.